Reconciling the historical divide between strategy process and strategy content. Issue 3 (11th October 2019) - Randall, Craig; Dent, Eric B.
Abstract : Purpose: Early works in strategic management described strategy process and were quickly followed by a plethora of strategy content articles focusing on tools, theories, frameworks and models for use in strategizing. Subsequently, strategy research and pedagogy diverged along these lines and the two streams have not been satisfactorily reconciled. As the process incorporates content and content requires process, this paper seeks to answer the question; can some relational consistency and historical reconciliation be developed? The purpose of this paper is to propose a process/content interrelation and a generic model of strategizing. Design/methodology/approach: The authors first identify the opportunity for this integration through the historical development of the two streams. The authors then review contemporary scholarly literature, strategic management textbooks and university syllabi to determine which elements of the strategy process and content are most frequently promulgated. Findings: The authors discover a generally ubiquitous core of concepts, but great inconsistency in how they are emphasized, linked and/or applied. Beyond these core concepts, faculty syllabi included a wide range of more idiosyncratic content (appearing very infrequently – possibly related to instructor research or interest areas), such as blue ocean or game theory. The authors then propose a 2 × 2 matrix with axes of the level of analysis and stage of activity. The authors provide a populated matrix and discuss the implications of this matrix for future scholarship and teaching. Originality/value: This paper begins a process of integrating the historical divide between strategy process and strategy content. It provides insights for classroom faculty, historians and practitioners.